Critical Evaluation of Chromebook Procurement in the Digitalization of Education Program Balancing Innovation and Policy Challenges - Reza Andrea; Jufrina Mandulangi; Aneke Yolly Punuindoong; Aziz Mukhamad Thoha; Hasbi Sjamsir; Aulia Khoirunnita (Research in Education, Technology, and Multiculture, 2026)
This paper critically evaluates Chromebook procurement in Indonesia’s education digitalization program by examining how procurement governance shapes corruption risks and shapes the conditions under which educational technology is implemented. Employing a qualitative case study approach, this research draws on secondary data from procurement documents, regulatory frameworks, media reports, and relevant academic literature, which were analyzed through content analysis and validated using source triangulation. The findings indicate that the most significant corruption risks emerged during the planning and technical specification stages, particularly through budget mark-ups, specification locking, restricted vendor competition, and informal negotiations among bureaucratic actors, suppliers, and external parties. Because this study does not collect perception data from teachers or students, the Technology Acceptance Model is used only as a conceptual lens for interpreting documented implementation conditions, such as internet dependence, uneven teacher readiness, and unequal access to digital resources, which may affect perceived usefulness and perceived ease of use. The study concludes that the digitalization of education should not be measured solely by the number of devices distributed, but by the transparency, accountability, and contextual relevance of procurement decisions. Strengthening oversight mechanisms, institutional integrity, and need-based planning is essential to ensure that digital technologies contribute to substantive educational improvement rather than serving merely as instruments of policy symbolism. Keywords: Chromebook procurement, Education digitalization, Corruption, Public procurement governance.